Serious adverse events and lifetime risk of reoperation after elective shoulder replacement: population based cohort study using hospital episode statistics for England - Craig, R; Lane, J; Carr, A; Furniss, D; Collins, G; Rees, J (BMJ Publishing Group, 2019)
Objectives To provide accurate risk estimates of serious adverse events following elective shoulder replacement surgery for arthritis, including age- and sex-specific estimates of the lifetime risk of revision surgery. Design Population-based cohort study. Setting Hospital Episode Statistics for NHS England including Civil Registration mortality data. Participants 74 163 patients underwent a shoulder replacement procedure between April 1998 and April 2017. After excluding patients aged less than 50, those with only revision surgery recorded, and procedures performed for acute trauma or bone tumours, there remained 58 054 elective shoulder replacements in 51 895 participants. Main outcome measures The lifetime risk of revision surgery was calculated using an actuarial life table approach and the cumulative probability method. Rates of serious adverse events are presented at 30 and 90 days post-surgery: pulmonary embolism, myocardial infarction, lower respiratory tract infection, acute kidney injury, urinary tract infection, cerebrovascular events, and death. The number of cases performed each year and Kaplan Meier estimates of revision risk at 3, 5, 10, and 15 years are reported as secondary outcomes. Results Between 1998 and 2017, the number of shoulder replacements performed per year increased 5.6 fold. Lifetime risks of revision surgery ranged from 1 in 37 (2.7%, 95% CI 2.6 to 2.8) in women aged 85 years and older to 1 in 4 (23.6%, 23.2 to 24.0) in men aged 55-59 years. The highest risks of revision occurred during the first five years. Within 30 days and 90 days of surgery respectively, the risk of any serious adverse event was 1 in 28 (3.5%, 3.4 to 3.7), and 1 in 22 (4.6%, 4.4 to 4.8). Within 30 days, the relative risk of pulmonary emboli compared to baseline population risk was 61. Serious adverse events were associated with increasing age, comorbidity, and male sex. 1 in 5 (21.2%, 17.9 to 25.1) of men aged 85 years and older experienced at least one serious adverse event within 90 days. Conclusions Younger patients, particularly men, need to be aware of a higher likelihood of early failure of their replacement and the need for further and more complex revision replacement surgery. All patients should be counselled about the risks of serious adverse events. These risks are higher than previously considered and for some, may outweigh any potential benefits. Our findings caution against unchecked expansion of shoulder replacement surgery in both younger and older patients. The more accurate, age- and sex-specific, estimates of risk from this study are long overdue and will improve shared decision making between patients and clinicians.